Friedrich Nietzsche’s Apollonian and Dionysian Dichotomy in Kate Chopin’s The Awakening - Kouachi , Rawiya (Milev Journal of Research and Studies, 2022)
Human nature is a thorny topic that triggers a myriad of discussions all over the world. In this regard, researchers endeavor to understand human behavior as a result of rational or emotional impulses. Accordingly, this article attempts to diagnose the controlling power of human nature in Kate Chopin’s The Awakening and the real cause of the characters’ downfall from Friedrich Nietzsche’s philosophical ideas. Hence, the analysis reveals that some characters’ behavior, like the protagonist Edna Pontellier and Victor Lebrun, is controlled by emotional Dionysian impulses; while, the behavior of Léonce Pontellier, Robert Lebrun, Mademoiselle Reisz and Adèle Ratignolle reflects rational Apollonian tendencies. Yet, most of the characters fail to make a balance between Apollonian and Dionysian characteristics that led to their tragic downfall inasmuch as the best life, for Nietzsche, demonstrates the combination of both Apollonian and Dionysian impulses. Therefore, human life is based on the harmony between Apollonian and Dionysian tendencies.